Dynamics of Clan Based Conflicts in Wajir County, Kenya - David Karienye; Prof Osman Warfa (Budapest International Research and Critics University, 2020)
Clannism is one of the key drivers of violent attacks in Northern Kenya. The causes of the persistent clan-based conflicts in Northern Kenya are not well known and ascertained. The rising incidents of violent attacks which clan-based conflict can be partially blamed, which this study attempted to explore. This underpins the need to conduct research in order to explore the drivers of clan-based conflict in Wajir county. The specific objective of the study was to assess the drivers of inter-clan and intra-clan-based conflicts in Wajir county, Kenya. The study adopted an exploratory research design. The study involved qualitative approach of data collection. The target population comprised of clan elders (Degodia, Ogaden and Ajuran), security agents, religious leaders and civil society organizations. A total of 31 respondents were interviewed who were selected using purposive and snowball approach. Interview guides were administered to the various respondents. The information obtained in the study was thematically analyzed according to the research questions. The study found that some of the key drivers of clan conflict in Wajir County include political influence, constituency boundaries, unequal sharing of county resources and competition over water and pasture. Findings from this study will be published to aid in disseminating information on the best ways to mitigate the clan-based conflict.